Production of monoclonal antibody against alkylhydroperoxide reductase - Mohammadian, Taher (Archives of Advances in Biosciences, 2013)
Development of a stool antigen immunoassay to detect Helicobacter pylori infection requires monoclonal antibody against the specific antigen. Alkylhydroperoxide reductase (AhpC) of Helicobacter pylori has been described as a specific and unique enzyme for H. pylori and therefore, both H. pylori AhpC and Anti-AhpC could be useful in the development of serologic and stool antigen tests, for detecting and monitoring H. pylori infection. The aims of this study were to prepare a monoclonal antibody against AhpC. Accordingly, The isolation and purification of AhpC from H. pylori were attempted by various techniques including ammonium sulfate precipitation, dialysis, preparative sodium dodecyl sulfate polyacrylamide gel electrophoresis and electroelution. Furthermore mice were immunized intraperitoneally with homogenized gel containing the AhpC band of protein extract of H. pylori in sodium dodecyl sulfate- polyacrylamide gel electrophoresis. The monoclonal antibody was produced using the hybridoma technique.One-dimensional preparative gel electrophoresis allows a single and short purification step, the high-resolution capacity of this technique leads to a high level of purity of the enzyme and consequently to a very high specificity of the antibody. The high specificity of antibody was identified by immune blotting in which the antibody reacted with the purified AhpC and whole cell protein extract from H. pylori in addition to the intact cells of H. pylori. This approach is simple, time and cost-saving for preparation of monoclonal antibody against AhpC of H. pylori.